Protocolos para a conservação do acervo Pedro Moraleida: critérios para uma arte nova - Tatiana Duarte Penna (2013)
This dissertation aimed to establish criteria for conservation and packaging in a contemporary collection - Pedro Moraleida Collection - made up of paintings and drawings in various media and dimensions. By means of the study of this collection, we attempt to make a retrieval of the memory of a visual artist who represents the 90's generation in Belo Horizonte, and by applying a methodology of documentation and a proposal of storage and packaging of this sometimes ephemeral art, it is possible to safeguard the intention of the artist and his poetic, seeking to establish new paradigms in relation to this current art.